Economic growth and distribution of income: A growth model to fit Ghanaian data - Nelson, Harumi T.; Roe, Terry L.; Diao, Xinshen (International Food Policy Research Institute, 2009)
The extent to which growth reduces poverty has been disputed for years, as has the controversy surrounding trade-offs between policies that seek growth and those that address equity. Structural models linking economic growth and the distribution of income and expenditure are relatively recent and have not been exploited. This paper exploits this literature by adapting and extending it to a multisector growth model with intermediate inputs, composite capital, and government revenue and expenditures, while accounting for income and expenditure, by quintile, of households in the modeled economy. The model is fit to Ghanaian data. We find that about 50 years are required to double income per worker, while lower- and upper-quintile levels of household income tend to converge modestly toward mean household income over time. Nevertheless, the dispersion of income remains relatively high in the long run. The sensitivity of these results to productivity shocks favoring agriculture shows that increasing labor productivity leads to growth with little change in the distribution of income relative to the base solution. Increasing land productivity and decreasing protection of the industrial sector do not alter the basic trends but do tend to cause the lower-income groups to fall further below ?new? mean income and the higher-income group to exceed mean income relative to the base solution.